Implementasi Konsep “Contemplative Art Practice” pada Perancangan Interior Creative Arts Center di Samarinda - Kristie Maria Gozali; Diana Thamrin; Lucky Basuki (Intra, 2018)
The existence of art as an expression of creativity as well as preservation of values and culture has an important role to achieve an ideal city. Unfortunately, society gives less attention to art communities, artist, and local art in Samarinda. Based on this phenomenon, the designer aims to design an education and recreation facilities to support art activities in Samarinda. As one of the local communities in Samarinda, Ladang Community becomes the background of the design project. “Interior Design of Creative Arts Center, as an education and recreation facility for Ladang Community in Samarinda” adopted Standford d’School design thinking process. Some of the design’s steps are: (1) Understand, (2) Observe, (3) Point of View, (4) Ideate, (5) Prototype, (6) Test, (7) Implement. “Contemplative Art Practice” concept is applied in the design, such as in space arrangement for each art activities. The concept was expected to create a creative space for art communities, artist, and public. Some facilities in the design include lobby, office, meeting room, mini library, painting studio, dance studio, auditorium, gift shop, nature studio, etc. From this project, the local of Samarinda was expected to give more appreciation to the local art and express their creativity.